Analysis of Benefits of Wood Products in Social Forestry Program in Perum Perhutani - Ary Widiyanto (Jurnal Agroforestri Indonesia, 2019)
Share of timber is the benefits obtained by farmers from the Community-Based Forest Management Program (PHBM). The purpose of this study is to analyze the benefits obtained by farmers from teak and pine wood at harvest time. Data collection was conducted by interview and recording methods. Data analysis was done by calculating the value of the timber received by farmers. The results showed that, first, during the 30 years of cooperation, pine wood revenue-sharing received by farmers was four times, three times from thinning and once from harvesting. Second, during 40 years of cooperation, teak wood revenue sharing received by farmers is eight times, namely seven times from thinning and once from harvesting. Third, in normal conditions without forest disturbance and an increase in the price of wood for the value of inflation then the timber yield pine received by farmers in the 30th year for pine and 40th year for teak respectively is around Rp. 24,937,500 and Rp. 130,100,000. Share of timber received by farmers every 5-10 years causes low community participation in PHBM. Therefore, PHBM needs to be expanded, not only limited to timber but also to non-timber forest products, which generate income every year.